Evaluation and improvement of Hi-Top Supermarket's product and facilities layout - Bascuñana, Marivi; Bautista, Ma. Rene.; Conde, Romul; Flora, Edna Ma. Clariss (Quezon City Department of Industrial Engineering and Operations Research, College of Engineering, University of the Philippines, 1991)
This paper aims to be able to improve the services/products and facilities layout of an existing supermarket, specifically HI-TOP Supermarket, located on Bohol Avenue, Quezon City. The study consisted of the collection of data including supermarket dimensions, products sold and feedback from shoppers through a survey. Using Systematic Layout Planning, the data obtained was evaluated and a new, improved layout was designed. This paper contains the evaluated data, the string diagrams and the activity relationship diagrams pertinent to the study. It also includes the final suggested layout and suggested guidelines on the improvement of the supermarket's physical arrangement, as well as a brief discussion on the principles of layout planning.
Keywords: Hi-Top Supermarket